2009
DOI: 10.1007/s00383-008-2309-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recurrence after inguinal herniotomy in boys

Abstract: Larger hernial sacs and sacs inadvertently opened during surgery are predictors of later recurrence. Low gestation and specific comorbidities were also associated with a higher likelihood of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 16 publications
5
15
1
1
Order By: Relevance
“…Consistent with our results, Vogels et al [12] concluded from a series of 2,471 primary herniotomies for boys that low gestational age and specific comorbidities may be associated with a higher likelihood of recurrence. Based on our experience with recurrence after laparoscopic hernia repair in children, the medial aspect of the internal inguinal ring is most crucial.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with our results, Vogels et al [12] concluded from a series of 2,471 primary herniotomies for boys that low gestational age and specific comorbidities may be associated with a higher likelihood of recurrence. Based on our experience with recurrence after laparoscopic hernia repair in children, the medial aspect of the internal inguinal ring is most crucial.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the traditional open herniotomy, at least for children of low body weight, are characterized by significantly high rates for recurrence, testicular hypotrophy, and atrophy or high testis that requires subsequent orchiopexy. Although the recurrence rate for laparoscopic inguinal hernia cases seems to remain elevated for older children [2,5,[10][11][12][13][14], our results for babies weighing 5 kg or less suggest a lower recurrence rate than that reported by Nagraj et al [1] for open herniotomy (2.0% vs 2.7%) in a comparable group of patients.…”
Section: Discussioncontrasting
confidence: 78%
“…However, there is a report of recurrence of inguinal hernia between 1 and 9% in different reports involving different age groups [21][22][23]. There were 17 recurrences, with an overall incidence of 0.69% [24]. There were 17 recurrences, with an overall incidence of 0.69% [24].…”
Section: Except Anesthetic Complications Recurrence Is the Most Freqmentioning
confidence: 99%
“…It was considered that large size of the hernia, premature state of the infant, history of incarceration and postoperative complications were associated with increased recurrence of hernia [8][9][10][11][12][13]. Extraperitoneal internal ring closures seemed to have a lower recurrence rate [5].…”
Section: Discussionmentioning
confidence: 99%